GALA DI NAGARI KAMPUANG TANGAH KABUPATEN AGAM - Ardo Satria (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
This article aims to describe the form of gala in Kampuang Tangah, Agam regency and categorize the address term from gala itself. Data collected by interview, field note and recording. This research uses descriptive-qualitative approach. The result of the data analysis are the form of gala consist of noun phrase with different formula. The address term using in gala is title only. Keyword : titles, form, fuction, meaning, value